Tetrapodal diazatriptycene enforces orthogonal orientation in self-assembled monolayers - Benneckendorf, Frank S.; Rohnacher, Valentina; Sauter, Eric; Hillebrandt, Sabina; Münch, Maybritt; Wang, Can; Casalini, Stefano; Ihrig, Katharina; Beck, Sebastian; Jänsch, Daniel; Freudenberg, Jan; Jaegermann, Wolfram; et al. (ACS applied materials & interfaces, 2020)
Conformationally rigid multipodal molecules should control the orientation and packing density of functional head groups upon self-assembly on solid supports. Common tripods frequently fail in this regard because of inhomogeneous bonding configuration and stochastic orientation. These issues are circumvented by a suitable tetrapodal diazatriptycene moiety, bearing four thiol-anchoring groups, as demonstrated in the present study. Such molecules form well-defined self-assembled monolayers (SAMs) on Au(111) substrates, whereby the tetrapodal scaffold enforces a nearly upright orientation of the terminal head group with respect to the substrate, with at least three of the four anchoring groups providing thiolate-like covalent attachment to the surface. Functionalization by condensation chemistry allows a large variety of functional head groups to be introduced to the tetrapod, paving the path toward advanced surface engineering and sensor fabrication.
Published: December 11, 2019
Gesehen am 08.04.2020